REGULATION OF THE AUTHORITY OF OJK INVESTIGATORS IN THE INVESTIGATION OF CRIMINAL ACTS IN THE FINANCIAL SERVICES SECTOR AFTER THE P2SK LAW - Dinda Suhartati; Frans Simangunsong (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The development of the financial services sector has been accompanied by increasingly complex financial crimes, necessitating a specialized investigative body with sufficient technical authority. This study aims to analyze the regulatory framework governing the investigative authority of the Financial Services Authority (OJK) Investigators in financial sector crimes based on the applicable normative framework. This research employs a normative juridical method with a statute approach and conceptual approach, utilizing library research through primary and secondary legal materials analyzed prescriptively with deductive reasoning. The study finds that OJK Investigators hold investigative authority of an attributive nature derived from Law Number 21 of 2011 and Law Number 4 of 2023, encompassing four dimensions of authority: the scope of criminal offenses, subjects, types of actions, and the timeframe of exercise. Following Constitutional Court Decision Number 59/PUU-XXI/2023, this authority shifted from a potentially exclusive character to one exercised coordinatively alongside the National Police without eliminating its attributive legal basis. The exercise of OJK investigative authority requires procedural compliance with the principle of legality as reinforced through the case review mechanism under Law Number 20 of 2025 on the Criminal Procedure Code, such that deviations from prescribed procedures may invalidate investigation results and serve as the basis for assessing the legality of investigative actions in the financial services sector.